2019
DOI: 10.23960/komputasi.v7i2.2423
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Kebutuhan Bahan Ajar Geometri Berbantuan Aplikasi Komputer

Abstract: This research aimed to find out the need for modules aided by computer applications in the geometry course at IAIN Metro. This research is a descriptive exploratory study. The method used in the form of a questionnaire which completed with interviews to get more in-depth results. Data obtained from the percentage of the results of the total number of responses for all respondents then analyzed descriptively qualitatively. The conclusion of this study is that it needs to be developed teaching materials in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
(2 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, learning by utilizing videos can maximize learning outcomes by up to 75 percent (Krisna & Marga, 2018). Several research results revealed that students need learning videos in spatial analytical geometry courses because the majority of students have difficulty visualizing in three dimensions (Ikashaum et al, 2019). Results of analysis of learning video needs that students need It was explained that…”
Section: Learning Video Of Third Dimensional Coordinate Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, learning by utilizing videos can maximize learning outcomes by up to 75 percent (Krisna & Marga, 2018). Several research results revealed that students need learning videos in spatial analytical geometry courses because the majority of students have difficulty visualizing in three dimensions (Ikashaum et al, 2019). Results of analysis of learning video needs that students need It was explained that…”
Section: Learning Video Of Third Dimensional Coordinate Systemmentioning
confidence: 99%
“…With all of the benefits of using instructional films, pupils can solve mathematical issues. (Dirgantoro et al, 2021;Sitinjak, 2022;Astra et al, 2014;Ikashaum et al, 2019). The ADDIE approach is useful to create educational videos.…”
Section: Introductionmentioning
confidence: 99%